Increasing the durability of cold forging dies hardening with intermediate tempering - D. M. Berdiev; R. K. Toshmatov; A. Kh. Abdullaev (Литьë и металлургия, 2022)
Based on studies of the tool wear nature for cold stamping, the expediency of using heat treatment by quenching with intermediate tempering has been established. Considering that the dislocation density changes little at 1100–1150 ºС, it was recommended this specific temperature range for heat treatment. Intermediate tempering at 450 ºС is the most preferable, as it provides not only dislocation structure stabilization, but also reduces internal stresses after the first hardening. This treatment increases the durability of the forging tool by 2–3 times.